Is Scholarly Refereeing Productive (at the Margin)? - Aboozar Hadavand; Daniel S. Hamermesh; Wesley W. Wilson (Institute of Labor Economics (IZA), 2019)
In economics many articles are subjected to multiple rounds of refereeing at the same journal, which generates time costs of referees alone of at least 50 million. This process leads to remarkably longer publication lags than in other social sciences. We examine whether repeated refereeing produces any benefits, using an experiment at one journal that allows authors to submit under an accept/reject (fast-track or not) or the usual regime. We evaluate the scholarly impacts of articles by their subsequent citation histories, holding constant their sub-fields, authors' demographics and prior citations, and other characteristics. There is no payoff to refereeing beyond the first round and no difference between accept/reject articles and others. This result holds accounting for authors' selectivity into the two regimes, which we model formally to generate an empirical selection equation. This latter is used to provide instrumental estimates of the effect of each regime on scholarly impact.
Keywords: A1; I2; 330; publishing; refereeing; citations